A adoção do comércio eletrônico em relação aos estágios de informatização: um estudo no setor metal-mecânico brasileiro - Boehs, Carlos Gabriel Eggert; Abib, Gustavo; Mazo, Miriam Stolses (Revista Gestão da Produção Operações e Sistemas, 2006)
The adoption of the information technology for new forms in the sales process is a reality. Its application carries strong advantages to be utilized by the companies, such as cost reduction, process agility and elimination of the intermediation. Connected with these arguments, the utilization of the e-commerce depends on the companies’ capacity to manage efficiently the assets and information technologies. The adoption of ecommerce practices in the Metal-Mechanic industry is the main purpose of this study, which had the collaboration of 174 small, medium and large Brazilian companies. The analyses of the results indicated a relation between the level of information technology (I.T.) adoption and the use of e-commerce, showing that the accumulated experience at the management of I.T. has a positive influence in e-commerce practices. Other analyzed data showed that small and large companies have a higher level of e-commerce practices. The study also verified that in companies of this segment the use of e-commerce is becoming more and more important, in addition to the traditional sales processes. Keywords: E-commerce; Information Technology; Sales Process.